Życie codzienne nauczycieli szkół powszechnych w Okręgu Mazurskim w świetle wspomnień i pamiętników (część II) - Radziszewska, Maria (Biuletyn Historii Wychowania, 2012)
The article concerns the problem of public school teachers’ daily lives in Masuria. The analysis took into account such components of everyday life as: travel to Warmia and Masuria, reasons for choosing the profession, education, work areas, the conditions and working methods, types of nourishment at school, the financial conditions of schools and some elements of private life. The issue of teachers’ daily lives deserves special attention because of the specific situation of Polish education in Warmia and Masuria in the school years 1944/1945 1945/1946. Teachers were mainly engaged in organizing Polish schools from the start in order to promote the Polish language among youth and children from different nationalities and cultures. Their daily lives were strongly influenced by determining the final borders of the District of Masuria, the action for preserving this land, the constant risk and problems with the staff, rooms and money. The article is not only about daily professional life (part I) but also about teachers’ personal lives (part II). The sphere of private life refers to issues such as food supplies, households, salaries, housing, family matters, forms of spending leisure time. There is certainly a need for broader studies using a variety of source materials. The sources of an autobiographical nature, memories and diaries, have been mainly used to present the issue.